Molecular cloning, functional expression, and gene silencing of two Drosophila receptors for the Drosophila neuropeptide pyrokinin-2. - Rosenkilde, C.; Cazzamali, G.; Williamson, M.; Hauser, F.; Sondergaard, L.; DeLotto, R.; Grimmelikhuijzen, C.J.P. (Biochemical and Biophysical Research Communications, 2003)
The database of the Drosophila Genome Project contains the sequences of two genes, CG8784 and CG8795, predicted to code for two structurally related G protein-coupled receptors. We have cloned these genes and expressed their coding parts in Chinese hamster ovary cells. We found that both receptors can be activated by low concentrations of the Drosophila neuropeptide pyrokinin-2 (CG8784, EC(50) for pyrokinin-2, 1x10(-9)M; CG8795, EC(50) for pyrokinin-2, 5 x 10(-10)M). The precise role of Drosophila pyrokinin-2 (SVPFKPRLamide) in Drosophila is unknown, but in other insects, pyrokinins have diverse myotropic actions and are also initiating sex pheromone biosynthesis and embryonic diapause. Gene silencing, using the RNA-mediated interference technique, showed that CG8784 gene silencing caused lethality in embryos, whereas CG8795 gene silencing resulted in strongly reduced viability for both embryos and first instar larvae. In addition to the two Drosophila receptors, we also identified two probable pyrokinin receptors in the genomic database from the malaria mosquito Anopheles gambiae. The two Drosophila pyrokinin receptors are, to our knowledge, the first invertebrate pyrokinin receptors to be identified.